Interleukin 35: Inhibitory regulator in monocyte-derived dendritic cell maturation and activation. (August 2018) - Chen, Xi; Hao, Shengnan; Zhao, Zhonghua; Liu, Jia; Shao, Qianqian; Wang, Fang; Sun, Dong; He, Ying; Gao, Wenjuan; Mao, Haiting
Highlights: IL-35 suppresses MoDC maturation. IL-35-treated MoDCs inhibit proliferation of CD4 + /CD8 + T cells. IL-35-treated MoDCs suppress polarization of Th1 and CD8 + T cells allogeneic response. IL-35 inhibits MoDC maturation through aberrant activation of STAT1/STAT3. Abstract: IL-35, a novel IL-12 family member, is a potent inhibitory cytokine predominantly produced by regulatory T and B lymphocytes that exerts optimal suppression in immune response. However, it remains unclear whether IL-35 plays an inhibitory role on human dendritic cells. In the present study, we focused on the possible immunosuppressive effect of IL-35 on the differentiation, maturation and function of monocyte-derived DCs (MoDCs). Addition of exogenous IL-35 was able to partially suppress MoDCs differentiation in vitro. Subsequently, LPS was used for the maturation of MoDCs and IL-35 was found to mainly restrain the maturation of MoDCs, characterized by the remarkable down-regulation of costimulatory molecules, CD83 and HLA-DR as well as a reduced production of pro-inflammatory cytokines (IL-12p70, IFN-γ, and TNF-α). Furthermore, IL-35-treated MoDCs exhibited strong inhibition in the proliferation of allogeneic CD4 + /CD8 + T lymphocytes. Meanwhile, IL-35-treated MoDCs also suppressed the polarization of naïve CD4 + T lymphocytes towards Th1 phenotype and impaired CD8 + T cells allogeneic responses. And the foregoing suppression of MoDCs maturation and function by IL-35 might be due to the aberrant activation of STAT1/STAT3 and inhibition of p38 MAPK/NF-κB signaling pathway. Our results demonstrated for the first time that IL-35 played a critical role in modulating not only adaptive immune response, but also innate immune response. The inhibitory effect of IL-35 on MoDCs maturation and function may facilitate the development of promising therapeutic interventions in tumors and other diseases.